AMP‐activated protein kinase activation in mediating phenylalanine‐induced neurotoxicity in experimental models of phenylketonuria. Issue 4 (11th December 2017) - Lu, Lihua; Ben, Xiaoming; Xiao, Lingling; Peng, Min; Zhang, Yongjun
Abstract: Phenylketonuria (PKU), one of the most prevalent autosomal recessive disorders of amino acid metabolism, is characterized by abnormal accumulation of phenylalanine, which can lead to intellectual disability. The main pathologic changes in the central nervous system of untreated phenylketonuric patients are reductions in the number of axons, dendrites, and synapses in the brain. Such alterations are thought to be mainly associated with the toxic effects caused by phenylalanine. However, the underlying molecular mechanisms have not been fully elucidated. The present study shows that a high concentration of phenylalanine remarkably inhibited neuronal neurite formation in vitro. Interestingly, AMP‐activated protein kinase (AMPK), the energy status sensor, was activated in cultured cerebral cortical neurons upon phenylalanine treatment. Pretreatment with an AMPK inhibitor ameliorated the reduction of neurite formation caused by phenylalanine. In addition, the levels of the phosphorylated AMPK, the active form of AMPK, were significantly higher in the cerebral cortices of PKU mice with elevated phenylalanine levels in this brain region compared to those in wild‐type control mice, whereas the density of dendritic spines on basal secondary dendrites of pyramidal neurons in prefrontal cortices of PKU mice was significantly decreased. Collectively, these findings indicate that AMPK activation is a key event in impaired neuronal dendritic development in PKU and consequently, a potential therapeutic target for developing neuroprotective strategies against phenylalanine‐evoked brain injury in PKU.